2021
DOI: 10.1080/09540121.2021.1922577
|View full text |Cite
|
Sign up to set email alerts
|

Symptom prevalence, burden and correlates among people living with HIV in Vietnam: a two-centre self-report study

Abstract: Physical and psychological symptoms among people living with HIV (PLWH) adversely affect quality of life and treatment adherence. Study objectives were: (i) to determine validity and reliability of a Vietnamese translation of the Memorial Symptom Assessment Scale-Short Form (MSAS-SF) among PLWH in Vietnam; (ii) to measure prevalence and burden of physical and psychological symptoms using the MSAS-SF including the Global Distress Index (GDI), Physical Distress subscale (PHYS), and Psychological Distress subscal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Pain is a common and distressing symptom among patients with cancer and patients with HIV/AIDS in Vietnam but remains poorly controlled. [1][2][3] Palliative care (PC) is an ethically necessary response to suffering associated with serious illness and a crucial component of health care systems. 4 In Vietnam, a survey conducted in 2004 in a tertiary cancer treatment center in Hanoi showed that approximately 50% of patients experienced moderate to severe pain, but only 1% experienced total relief from analgesic therapy, and 40% received partial relief.…”
Section: Introductionmentioning
confidence: 99%
“…Pain is a common and distressing symptom among patients with cancer and patients with HIV/AIDS in Vietnam but remains poorly controlled. [1][2][3] Palliative care (PC) is an ethically necessary response to suffering associated with serious illness and a crucial component of health care systems. 4 In Vietnam, a survey conducted in 2004 in a tertiary cancer treatment center in Hanoi showed that approximately 50% of patients experienced moderate to severe pain, but only 1% experienced total relief from analgesic therapy, and 40% received partial relief.…”
Section: Introductionmentioning
confidence: 99%
“…Levy et al ( 8 ) examined the associations between psychosocial risk factors and subclinical atherosclerosis among women living with HIV and among HIV-negative women and concluded that psychological symptoms could increase the risk of atherosclerosis in women living with HIV. PLWH living in poor areas also have a higher number of mental disorders or psychological symptoms because they tend to have less access to health care services ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%